Behavior of circular ice-filled self-luminous FRP tubular stub columns under axial compression. (30th January 2020) - Wang, Yanlei; Chen, Guipeng; Wan, Baolin; Cai, Gaochuang; Zhang, Yiwen
Highlights: Material-level investigations are conducted on self-luminous FRP laminates. Circular ice-filled self-luminous FRP tubular (IFSFT) column is newly proposed. Self-luminous powders have little effect on the compressive behavior of IFSFT. Compressive strength of confined ice is increased with the number of FRP layers. Equations for evaluating axial bearing capacities of IFSFT columns are proposed. Abstract: This paper proposes an innovative ice-filled self-luminous fiber-reinforced polymer (FRP) tubular (IFSFT) column for temporary structures in cold regions. The proposed column possesses a good combination of the advantages of FRP tube and natural ice, as well as provides itself with aesthetic features or other service functions due to the self-luminous feature of the outer FRP tube in darkness. This paper presents an experimental study on tensile and luminance properties of FRP laminates modified with self-luminous powders, and axial compressive behavior of circular IFSFT stub columns and ice-filled FRP tubular (IFFT) stub columns. Experimental results indicate that the addition of self-luminous powders into FRP composites has little influence on their tensile properties as well as axial compressive behavior of IFSFT stub columns. Compressive strength, peak strain and elastic modulus of the confined ice cores in IFFT and IFSFT specimens have been significantly improved compared with those of unconfined plain ice. A simplified equation for evaluating axial bearing capacity of IFFT and IFSFT stub columns is proposed with a reasonable accuracy.